Experimenting with Farmers' Capacity and Social Institutions Building for ensuring Village Level Seed Sufficiency: A Case of Chickpea (Cicer arietinum L) in India - Shantanu Kumar Dubey , S. K. Singh , S. N. Nigam , Uma Sah , M. Ali , and A. S. Yadav, (Indian Journal of Extension Education, 2015)
Building farmers' capacity to experiment with the recommended technologies and at the same time facilitating them forinstitutionalizing their efforts requires constant validation, consolidation and upscaling. An action research wasconducted to empirically probe how the recommended and improved seed varieties may appear if looked with farmers'lens and how to a large extent the farmers' preferred varieties may reach, while using the interventions of institutionalbackstopping, capacity building, hand holding and enabling. Chickpea is a major pulse crop of India. However, itsproductivity is restricted around 896 kg/ha, over the past several decades. Local landraces and varietal admixture areinfluencing the chickpea cultivation in the country. One of the major reasons for low productivity of chickpea is the nonavailability of quality seed of improved varieties among the farmers. In the present paper, the experiences of farmerparticipatory chickpea seed production in districts of Fatehpur and Kanpur Dehat in Uttar Pradesh state of India have beenshared. Through farmer-participatory varietal selection trials, farmers identified DCP 92-3 and JG 16 varieties, as theirpreferred choices. These varieties were preferred because of its high yield, attractive seed size, seed color, better taste andcooking quality. Farmers were organized to form cooperative societies to undertake seed production, processing andmarketing at the local level. They were also linked with the public sector seed producing agencies to participate in theformal seed production program. The B:C ratio of seed production of DCP 92-3 and JG 16 variety was 2.94 and 3.18 ascompared to 2.15 of the local chickpea variety sold as grain. Village level seed production not only addressed the issue ofshortage of quality seeds but also brought higher incomes to farmers leading to their improved livelihood.